Le polymorphisme de l’ADN mitochondrial révèle une différenciation génétique entre certains groupes ethniques de la population de Jerba - Yacoubi Loueslati, Besma; Ennafaa, Hajer; Ben Amor, Mohamed; Heyer, Evelyne; Langaney, André; Ben Ayed, Farhat (Archives de l'Institut Pasteur de Tunis, 1998)
Jerba is an island situated in the South - East of Tunisia were some ethnic groups (Arabs, Berbers, Blacks, Jewishs and others) cohabit for centuries. The religion and cultural differences have represented an obstacle to a mixture between these groups.
Keywords: Génétique – Djerba

Étude du polymorphisme des immunoglobulines et de l’ADN mitochondrial dans la population de l’île de Jerba - Yacoubi Loueslati, Besma (Faculté des Sciences Mathématiques, Physiques et Naturelles de l’Université de Tunis, 1999)
Keywords: Génétique – Djerba